Peran Komoditas Ekspor dalam Mendukung Pertumbuhan Ekonomi Indonesia - Nelly Ervina; Joni Wilson Sitopu; Muhammad Yudistira Arya Maulana; Erna Kustyarini; Widyatmoko Widyatmoko (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
This research aims to determine the role of export commodities in supporting Indonesia's economic growth. The background to this research illustrates the importance of the influence of exports on economic growth in Indonesia. The method used in this research is the literature study research method. The literature study in this research is a series of activities relating to methods of collecting library data, reading and taking notes, as well as managing research data objectively, systematically, analytically and critically about the role of export commodities in supporting Indonesia's economic growth. Export commodities play an important role in supporting Indonesia's economic growth in 2023. Contribution to GDP, Job Creation, Encouraging Investment, Supporting Macroeconomic Stability.